Dysregulated Neurovascular Control Underlies Declining Microvascular Functionality in People With Non-alcoholic Fatty Liver Disease (NAFLD) at Risk of Liver Fibrosis - Clough, Geraldine F.; Chipperfield, Andrew J.; Thanaj, Marjola; Scorletti, Eleonora; Calder, Philip C.; Byrne, Christopher D. (Frontiers in Physiology, 2020)
Background/aims Increasing evidence shows that non-alcoholic fatty liver disease (NAFLD) is associated with dysregulation of microvascular perfusion independently of established cardio-metabolic risk factors. We investigated whether hepatic manifestations of NAFLD such as liver fibrosis and liver fat are associated with microvascular haemodynamics through dysregulation of neurovascular control. Methods Microvascular dilator (post-occlusive reactive hyperaemia) and sympathetically mediated constrictor (deep inspiratory breath-hold) responses were measured at the forearm and finger respectively, using laser Doppler fluximetry. Non-linear complexity-based analysis was used to assess the information content and variability of the resting blood flux (BF) signals, attributable to oscillatory flow-motion activity, over multiple sampling frequencies Results Measurements were made in 189 adults (113 men) with NAFLD, with (n= 65) and without (n=124) type 2 diabetes mellitus (T2DM), age = 50.9±11.7 y (mean±SD). Microvascular dilator and constrictor capacity were both negatively associated with age (r=-0.178 p=0.014 and r=-0.201 p=0.007, respectively) and enhanced liver fibrosis (ELF) score (r=-0.155 p=0.038 and r=-0.418, p<0.0001, respectively). There was no association with measures of liver fat, obesity or T2DM. Lempel-Ziv complexity (LZC) and sample entropy (SE) of the BF signal measured at the two skin sites were associated negatively with age (p<0.01 and p<0.001) and positively with ELF score (p<0.05 and p<0.0001). In individuals with an ELF score ≥7.8 the influence of both neurogenic and respiratory flow-motion activity on LZC was up-rated (p<0.0001). Conclusions Altered microvascular network functionality occurs in adults with NAFLD suggesting a mechanistic role for dysregulated neurovascular control in individuals at risk of severe liver fibrosis.